METHODS OF DEVELOPMENT OF SOCIAL LINGUISTIC CULTURE IN RUSSIAN LANGUAGE CLASSES - Муминджанова Саида Хаитматовна (Bright Mind Publishing, 2025)
This article examines the methodology of development of socio-linguistic culture in the Russian language classes. The main theoretical and methodological aspects of this problem are analyzed, and the most effective approaches and methods are proposed. The main attention is paid to the development of communication skills, culture of speech and intercultural competence of students effectively conduct classes and achieve successful results.